Active strategic information systems and their role in promoting Entrepreneurial Orientation: An Applied research in Iraqi Private Banks in Baghdad - Alazzawi, Firas Raheem Younis (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the research is to answer the following question: Is it possible to strengthen the entrepreneurial orientation of the Iraqi private banks in the city of Baghdad in light of Active strategic information systems? In order to achieve the objectives of the research has developed a questionnaire designed for this purpose and then analysis has been tested in the Iraqi private banks in the city of Baghdad, so it was chosen (22) banks and commercial special in the city of Baghdad as a sample of research, the choice was based on the criterion of availability of information systems and strategic use In its banking industry, On the b(ASIS) of the scheme the default search, which takes into account the nature and dimensions of the relationships between the variables of Active strategic information systems represented by (open system, and human relations, internal processes, and the goal of rational) and the entrepreneurial orientation defined by (Innovativeness, and Pro-activeness, and Risk-taking, Competitive aggressiveness, and Autonomy) in the Iraqi private banks in the city of Baghdad, and guided by this scheme has sought research to test five hypotheses Head on the relationships of association and relationships influence between research variables so as to answer questions related to the problem of research and reach the goals set, so it has been tested using Some statistical methods, They’re: Kolmogorov-Smirnov test; Multicollinearity test; bivariate pearson correlation test; simple linear regression analysis, and interpretation coefficient (R2) The availability of Active strategic information systems and the entrepreneurial orientation appeared in the researched banks at high rates, as the sample answers to all questions related to these two variables or their sub-variables were highly consistent, and this indicates the astounding interconnectedness between their variables as they support one another in those banks. The strategic information systems variable at the total level or the level of its sub-variables also showed positive significant influence relationships at the level of (0.05) with the variable of the entrepreneurial trend and its sub-dimensions, and the percentage of these honest relationships constituted (100%) of the total.Keywords:, , ,,,